Solar cell and method for manufacturing solar cell

By maintaining a controlled water vapor concentration range within the sealed space of perovskite solar cells, the durability and stability issues associated with water vapor reaction are addressed, enhancing the solar cells' performance and longevity.

JP2025063285AActive Publication Date: 2025-04-15PANASONIC HOLDINGS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025009798
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-21
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2042-03-11

AI Technical Summary

Technical Problem

Perovskite solar cells face durability issues due to water vapor reacting with the perovskite compounds, forming insulating materials that inhibit photogenerating carrier transfer, leading to degradation of solar cell properties.

Method used

The solar cells are designed with a sealing structure that maintains a specific range of water vapor concentration (100 ppm to 5000 ppm) within the sealed space, while keeping the oxygen concentration below 2 ppm, to enhance the durability and stability of the solar cells.

Benefits of technology

This configuration effectively suppresses photodegradation and thermal degradation, improving the durability and stability of the solar cells, and allowing for efficient moisture management to prevent reaction with the photoelectric conversion material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063285000001_ABST
    Figure 2025063285000001_ABST
Patent Text Reader

Abstract

To improve the durability of solar cells.SOLUTION: A solar cell 1000 includes a support material 2, a photoelectric conversion element 1, and a sealing material 3. The photoelectric conversion element 1 is disposed inside a sealed space sealed by the support material 2 and the sealing material 3. The photoelectric conversion element 1 includes a first electrode, a photoelectric conversion layer, and a second electrode, in this order. The value obtained by dividing the amount of water vapor in the sealed space by the surface area of the face of the photoelectric conversion element facing the sealed space is 2.3×10-6 mol / m2 or more and 1.2×10-4 mol / m2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to solar cells and methods for manufacturing solar cells.

[0002] In recent years, composition formula ABX 3 Research and development is underway on perovskite solar cells that use perovskite-type crystals represented by the formula (A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and similar structures (hereinafter referred to as "perovskite compounds") as photoelectric conversion materials. Various efforts are being made to improve the photoelectric conversion efficiency and durability of perovskite solar cells.

[0003] Non-Patent Document 1 reports that water vapor in the atmosphere reacts with perovskite compounds, and as a result, substances that do not contribute to power generation, such as lead iodide, methylammonium iodide, or hydrates, are formed on the surface or grain boundaries of the perovskite compounds. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-103450 A [Non-patent literature]

[0005] [Non-Patent Document 1] Q. Sun, et al., Advanced Energy Materials, July 2017, Vol. 7, p. 1700977. [Non-Patent Document 2] Taka.T, Synthetic Metals, January 1993, Volume 57, p.5014. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present disclosure is to improve the durability of solar cells. [Means for solving the problem]

[0007] The solar cell of the present disclosure comprises: supporting material, A photoelectric conversion element, and a sealing material; the photoelectric conversion element is disposed inside a sealed space sealed by the support material and the sealing material, the photoelectric conversion element includes a first electrode, a photoelectric conversion layer, and a second electrode in this order; The value obtained by dividing the amount of water vapor in the sealed space by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space is 2.3×10 -6 mol / m 2 Greater than or equal to 1.2×10 -4 mol / m 2 The following is the result. Effect of the Invention

[0008] The present disclosure may improve the durability of solar cells. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram showing a schematic configuration of a solar cell 1000 according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic configuration of a first configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a cross-sectional view showing a schematic configuration of a second configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure. [Figure 4] FIG. 4 is a cross-sectional view showing a schematic configuration of a third configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure. [Diagram 5] FIG. 5 is a graph showing the water vapor concentration dependence of normalized photoelectric conversion efficiency of the solar cells of Example 1, Example 4, Example 6, and Comparative Example 1. [Figure 6]FIG. 6 is a graph showing the dependence of normalized photoelectric conversion efficiency of the solar cells of Example 1, Example 4, Example 6, and Comparative Example 1 on the amount of water vapor. [Figure 7] FIG. 7 is a graph showing the water vapor concentration dependence of normalized photoelectric conversion efficiency of the solar cells of Example 2, Example 3, Example 5, Example 7, and Comparative Example 2. [Figure 8] FIG. 8 is a graph showing the water vapor amount dependence of normalized photoelectric conversion efficiency of the solar cells of Example 2, Example 3, Example 5, Example 7, and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Knowledge that formed the basis of this disclosure> As reported in Non-Patent Document 1, perovskite compounds containing lead react with water to form substances that do not contribute to power generation, such as lead iodide, methylammonium iodide, or hydrates, on the surface or grain boundaries of the perovskite compound. These reaction products are highly insulating substances. Therefore, when a large amount of these reaction products are formed, the movement of photogenerated carriers is hindered, which causes a problem of deteriorating the characteristics of the perovskite solar cell. For this reason, perovskite solar cells are generally used in a nitrogen atmosphere with as little water as possible around them (for example, water vapor concentration of 0.1 ppm or less in volume fraction). In this specification, the water vapor concentration and oxygen concentration described below all refer to volume fraction concentrations.

[0011] Patent Document 1 discloses a perovskite solar cell having a sealing structure, in which oxygen and moisture are contained in the sealed space. It is disclosed that the heat resistance of the solar cell is improved by controlling the oxygen concentration in the space to 5% or more and the moisture concentration (volume fraction) to 300 ppm or less. However, Non-Patent Document 1 reports the effect of oxygen on the solar cell in addition to the above-mentioned degradation of the solar cell characteristics due to water vapor. Specifically, Non-Patent Document 1 discloses that the normalized photoelectric conversion efficiency of the perovskite solar cell after the light irradiation test decreases monotonically as the oxygen concentration increases from 1% to 20%, based on the case where the oxygen concentration around the solar cell is 0%. In this way, Non-Patent Document 1 reports that the light resistance decreases at an oxygen concentration of 5%. Therefore, it is predicted that it is difficult to achieve both thermal stability and light stability at an oxygen concentration of 5% or more.

[0012] Non-Patent Document 2 discloses that the electrical conductivity of a π-conjugated polymer, which is a hole transport material, is improved by coordinating water near the main chain of the polymer. However, there have been no reports to date that water vapor improves thermal stability and light stability, and the presence of water vapor has been considered to be a factor that reduces durability.

[0013] As described above, there have been no reports showing that the presence of water vapor contributes to improving the photostability and thermal stability, which are important in practical use.

[0014] In view of these prior arts, the present inventors have conducted detailed investigations into the threshold water vapor concentration, i.e., the water vapor concentration value at which the effect on the durability of the solar cell becomes significant, while suppressing the oxygen concentration in the sealed space to 2 ppm or less. As a result, it has been found that an optimal range for the durability of the solar cell exists between 0% and 1% water vapor concentration. Specifically, it has been found that in a solar cell having a sealed structure, when the water vapor concentration in the sealed space is in the range of 100 ppm or more and 5000 ppm or less, the photoelectric conversion efficiency after the light irradiation test and the photoelectric conversion efficiency after the heat resistance test are improved. Furthermore, it has been found that when the water vapor concentration in the sealed space is in the range of 100 ppm or more and 1000 ppm or less, the photoelectric conversion efficiency after the light irradiation test and the photoelectric conversion efficiency after the heat resistance test are further improved. Therefore, the photostability and the thermal stability of the solar cell can be achieved simultaneously when the water vapor concentration in the sealed space is in the range of 100 ppm or more and 5000 ppm or less, and can be further improved when the water vapor concentration in the sealed space is in the range of 100 ppm or more and 1000 ppm or less.

[0015] <Embodiments of the present disclosure> A solar cell according to an embodiment of the present disclosure includes a support material, a photoelectric conversion element, and a sealing material. The photoelectric conversion element is disposed inside a sealed space sealed by the support material and the sealing material. The photoelectric conversion element includes a first electrode, a photoelectric conversion layer, and a second electrode, in this order. The oxygen concentration in the sealed space is less than 10 ppm, and the water vapor concentration in the sealed space is 100 ppm or more and 5000 ppm or less.

[0016] According to the above-mentioned configuration, it is possible to suppress the photodegradation phenomenon and the thermal degradation phenomenon induced by defects in the photoelectric conversion material, and therefore it is possible to improve the durability of the solar cell.

[0017] In addition, for example, when the photoelectric conversion element further comprises a hole transport layer, the water vapor concentration in the sealed space is within the above range, so that the moisture is coordinated to the hole transport material while suppressing the reaction of the moisture with the photoelectric conversion material, thereby improving the conductivity of the hole transport layer. This improves the conductivity of the solar cell. As a result, holes can be efficiently extracted, so that recombination at the interface is less likely to occur. Therefore, for example, when the photoelectric conversion element further comprises a hole transport layer, the above configuration can further improve the durability of the solar cell.

[0018] In the solar cell according to the present embodiment, the water vapor concentration in the sealed space may be not less than 100 ppm and not more than 1000 ppm.

[0019] According to the above-mentioned configuration, the structural change of the photoelectric conversion material induced by heat and the structural change of the photoelectric conversion material induced by light are less likely to occur, and therefore, according to the above-mentioned configuration, the thermal stability and the light stability of the solar cell can be further improved.

[0020] In the solar cell according to this embodiment, the water vapor concentration in the sealed space may be more than 300 ppm.

[0021] As described above, the solar cell according to this embodiment has an oxygen concentration in the sealed space of less than 10 ppm. The low oxygen concentration of the sealed space of less than 10 ppm improves the light resistance of the solar cell, making it possible to achieve both thermal stability and light stability. To further improve light resistance, the oxygen concentration in the sealed space may be 2 ppm or less.

[0022] The water vapor concentration in the sealed space can be measured by an atmospheric pressure ionization mass spectrometer and gas chromatography. As a specific example, for example, an atmospheric pressure ionization mass spectrometer (API-TDS600, manufactured by API Japan) is used to destroy a sample package (i.e., a solar cell module) in a destruction chamber under a purified argon gas atmosphere, and the gas components in the package (i.e., the gas components in the sealed space) are detected, and the gas components in the package are quantitatively measured using a separately prepared calibration curve. This makes it possible to measure the gas components in the sealed space. Note that the gas in the sealed space can be collected by extracting the gas in the sealed space with a syringe, in addition to destroying the sample package in the destruction chamber as described above.

[0023] The oxygen concentration in the sealed space can be measured by an atmospheric pressure ionization mass spectrometer, gas chromatography, an electrochemical oxygen concentration meter, etc. The method for recovering the gas in the sealed space is, for example, the same as the method for measuring the water vapor concentration described above.

[0024] Here, as an example, a method is described in which the gas contained in the sealed space of the solar cell is discharged into a closed space such as the destruction chamber, and the water vapor concentration and oxygen concentration in the discharged gas are measured by an atmospheric pressure ionization mass spectrometer. For example, a solar cell module is placed in a chamber filled with an inert gas such as argon or krypton. The module is broken in the chamber to discharge the gas contained in the sealed space of the solar cell. Next, the gas in the chamber is quantitatively analyzed by an atmospheric pressure ionization mass spectrometer. The oxygen concentration can be obtained by quantifying all components in the gas in the chamber and calculating the ratio of oxygen to the total amount. Examples of gases contained in the sealed space other than water vapor and oxygen include inert gases such as nitrogen and rare gases, and carbon dioxide. Note that if the sealed space contains the same type of inert gas as the inert gas filling the chamber used for gas analysis, accurate gas analysis may be difficult. Therefore, when the type of gas contained in the sealed space is unknown, two identical solar cell modules are prepared, and different types of inert gas are used to fill the chamber, and the gas analysis is performed for each of the two solar cell modules using the above procedure.The composition of the gas contained in the sealed space can be determined by comparing the two analysis results. The partial pressure of water vapor in the sealed space is 1×10 -4 ATM or more and 5 x 10 -3 atm, 1×10 -4 atm or more and 1×10 -3 It may also be an ATM.

[0025] According to the above-mentioned configuration, it becomes easier to suppress the photodegradation phenomenon and the thermal degradation phenomenon induced by defects in the photoelectric conversion material, and therefore the durability of the solar cell can be improved.

[0026] When the solar cell of the present disclosure is fabricated under atmospheric pressure, the pressure in the sealed space is approximately atmospheric pressure. In this case, the partial pressure of water vapor in the sealed space is 1×10 -4 atm or more and 1×10 -3 It becomes ATM.

[0027] The partial pressure of water vapor in the sealed space can be calculated from the gas state equation by, for example, measuring the mass or molar concentration of the gas containing water vapor in the sealed space using the above-mentioned water vapor concentration measurement method, and further measuring the volume of the sealed space. The volume of the sealed space can be estimated, for example, by injecting a liquid into the sealed space. Alternatively, the volume can be estimated by disassembling the solar cell and measuring the shape of the space. The various measurements described above are usually performed at room temperature, but this is not limited to this. That is, in order to take into account the effects of adsorption and desorption of gas in the sealed space, they may be performed at a temperature that simulates an actual operating environment.

[0028] Modifications of the solar cell according to the embodiment of the present disclosure will be described. Duplicate descriptions may be omitted as appropriate.

[0029] As described above, the solar cell of the present disclosure includes a support material, a photoelectric conversion element, and a sealing material, and the photoelectric conversion element is disposed inside a sealed space sealed by the support material and the sealing material. The photoelectric conversion element includes a first electrode, a photoelectric conversion layer, and a second electrode, in this order. The amount of water vapor in the sealed space per surface area of ​​the surface of the photoelectric conversion element facing the sealed space is 2.3×10 -6 mol / m 2 Greater than or equal to 1.2×10 -4 mol / m 2 That is, the value obtained by dividing the amount of water vapor in the sealed space by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space may be 2.3×10 -6 mol / m 2 Greater than or equal to 1.2×10 -4 mol / m 2 This makes it possible to suppress deterioration of the solar cell due to long-term operation.

[0030] In order to further suppress deterioration due to long-term operation of the solar cell, the amount of water vapor in the sealed space per surface area of ​​the photoelectric conversion element facing the sealed space is set to 2.3 × 10 -6 mol / m 2 Greater than or equal to 2.3 x 10 -5 mol / m2 It may be the following.

[0031] In order to suppress deterioration due to oxygen, the amount of oxygen in the sealed space per surface area of ​​the photoelectric conversion element facing the sealed space is set to 7.0 x 10 -5 mol / m 2 That is, the value obtained by dividing the amount of oxygen in the sealed space by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space may be 7.0×10 -5 mol / m 2 It may be the following.

[0032] In the photoelectric conversion element, the main surface of the first electrode may face the support material, or the main surface of the second electrode may face the support material.

[0033] The solar cell of the present disclosure can be produced, for example, by the following method.

[0034] First, a photoelectric conversion element is produced by the method described below.

[0035] The obtained photoelectric conversion element is sealed with a sealant in a glove box in which the oxygen concentration is adjusted.

[0036] The oxygen concentration in the glove box is less than 10 ppm in volume fraction, and the water vapor concentration is 100 ppm or more and 5000 ppm or less in volume fraction. Alternatively, the amount of water vapor in the sealed space per surface area of ​​the surface of the photoelectric conversion element facing the sealed space is 2.3×10 -6 mol / m 2 Greater than or equal to 1.2×10 -4 mol / m 2 It has been adjusted as follows:

[0037] In this manner, a solar cell having the desired oxygen concentration and water vapor concentration is obtained.

[0038] As described above, a solar cell may be produced by sealing a photoelectric conversion element having a first electrode, a photoelectric conversion layer, and a second electrode in this order in an atmosphere having an oxygen concentration of less than 10 ppm by volume fraction and a water vapor concentration of 100 ppm or more and 5000 ppm or less by volume fraction.

[0039] FIG. 1 is a diagram showing a schematic configuration of a solar cell 1000 according to an embodiment of the present disclosure.

[0040] The solar cell 1000 according to this embodiment includes a photoelectric conversion element 1, a support material 2, and a sealing material 3. The photoelectric conversion element 1 is disposed inside a sealed space sealed by the support material 2 and the sealing material 3.

[0041] The photoelectric conversion element 1 may be in contact with the support material 2 .

[0042] The support material 2 and the sealing material 3 may be made of the same material. The material may have, for example, a gas barrier function. The material may be glass.

[0043] Hereinafter, the photoelectric conversion element 1 will be described in more detail using first to third configuration examples. Note that the photoelectric conversion element 1 is not limited to the photoelectric conversion elements of the following first to third configuration examples.

[0044] FIG. 2 is a cross-sectional view showing a schematic configuration of a first configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure.

[0045] The photoelectric conversion element 100 of the first configuration example includes, in this order, a substrate 4, a first electrode 5, an electron transport layer 6, a photoelectric conversion layer 7, a hole transport layer 8, and a second electrode 9. Like the photoelectric conversion element 100 of the first configuration example, the photoelectric conversion element 1 in the solar cell 1000 according to this embodiment may further include an electron transport layer between the first electrode and the photoelectric conversion layer, or may further include a hole transport layer between the photoelectric conversion layer and the second electrode.

[0046] When light is irradiated onto the photoelectric conversion element 100, the photoelectric conversion layer 7 absorbs the light and generates excited electrons and holes. The excited electrons pass through the electron transport layer 6 and move to the first electrode 5. Meanwhile, the holes generated in the photoelectric conversion layer 7 move to the second electrode 9 via the hole transport layer 8. This allows the photoelectric conversion element 100 to extract a current from the first electrode 5 as a negative electrode and the second electrode 9 as a positive electrode.

[0047] The photoelectric conversion element 100 may or may not have a substrate 4.

[0048] The photoelectric conversion element 100 may or may not have an electron transport layer 6. When the photoelectric conversion element 100 has the electron transport layer 6, electrons can be efficiently transferred to the first electrode 5. As a result, the photoelectric conversion element 100 can efficiently extract a current.

[0049] The photoelectric conversion element 100 may or may not have a hole transport layer 8. When the photoelectric conversion element 100 has the hole transport layer 8, holes can be efficiently moved to the second electrode 9. As a result, the photoelectric conversion element 100 can efficiently extract a current.

[0050] The photoelectric conversion element 100 can be produced, for example, by the following method.

[0051] First, the first electrode 5 is formed on the surface of the substrate 4 by chemical vapor deposition, sputtering, or the like. Next, the electron transport layer 6 is formed by chemical vapor deposition, sputtering, solution coating, or the like. Next, the photoelectric conversion layer 7 is formed on the electron transport layer 6. The photoelectric conversion layer 7 may be formed by, for example, a solution coating method, a printing method, or a vapor deposition method. Also, for example, a perovskite compound cut to a predetermined thickness may be placed on the electron transport layer 6 as the photoelectric conversion layer 7. Next, the hole transport layer 8 is formed on the photoelectric conversion layer 7 by chemical vapor deposition, sputtering, solution coating, or the like. Next, the second electrode 9 is formed on the hole transport layer 8 by chemical vapor deposition, sputtering, solution coating, or the like. In this manner, the photoelectric conversion element 100 is obtained.

[0052] FIG. 3 is a cross-sectional view showing a schematic configuration of a second configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure.

[0053] The photoelectric conversion element 200 of the second configuration example includes a substrate 4, a first electrode 5, an electron transport layer 6, a porous layer 10, a photoelectric conversion layer 7, a hole transport layer 8, and a second electrode 9, in this order. Like the photoelectric conversion element 200 of the second configuration example, the photoelectric conversion element 1 in the solar cell 1000 according to this embodiment may further include a porous layer. The porous layer is disposed, for example, between the electron transport layer and the photoelectric conversion layer.

[0054] The porous layer 10 includes a porous body. The porous body includes voids.

[0055] The photoelectric conversion element 200 may or may not have a substrate 4.

[0056] The photoelectric conversion element 200 may or may not have an electron transport layer 6. When the photoelectric conversion element 200 does not have the electron transport layer 6, the porous layer 10 is disposed between the first electrode 5 and the photoelectric conversion layer 7. When the photoelectric conversion element 200 has the electron transport layer 6, electrons can be efficiently transferred to the first electrode 5. As a result, the photoelectric conversion element 200 can efficiently extract a current.

[0057] The photoelectric conversion element 200 may or may not have a hole transport layer 8. When the photoelectric conversion element 200 has the hole transport layer 8, holes can be efficiently moved to the second electrode 9. As a result, the photoelectric conversion element 200 can efficiently extract a current.

[0058] FIG. 4 is a cross-sectional view showing a schematic configuration of a third configuration example of the photoelectric conversion element 1 in the solar cell 1000 according to an embodiment of the present disclosure.

[0059] The photoelectric conversion element 300 of the third configuration example includes a substrate 4, a first electrode 5, an electron transport layer 6, a porous layer 10, an intermediate layer 11, a photoelectric conversion layer 7, a hole transport layer 8, and a second electrode 9, in this order. Like the photoelectric conversion element 300 of the third configuration example, the photoelectric conversion element 1 in the solar cell 1000 according to this embodiment may further include an intermediate layer. The intermediate layer is disposed, for example, between the porous layer and the photoelectric conversion layer.

[0060] The photoelectric conversion element 300 may or may not have a substrate 4.

[0061] The photoelectric conversion element 300 may or may not have the electron transport layer 6. When the photoelectric conversion element 300 has the electron transport layer 6, electrons can be efficiently transferred to the first electrode 5. As a result, the photoelectric conversion element 300 can efficiently extract a current.

[0062] The photoelectric conversion element 300 may or may not have a hole transport layer 8. When the photoelectric conversion element 300 has the hole transport layer 8, holes can be efficiently moved to the second electrode 9. As a result, the photoelectric conversion element 300 can efficiently extract a current.

[0063] The photoelectric conversion element 300 may or may not have the porous layer 10. When the photoelectric conversion element 300 does not have the porous layer 10, the intermediate layer 11 is disposed between the electron transport layer 6 and the photoelectric conversion layer 7.

[0064] Each component of the photoelectric conversion element will be specifically described below.

[0065] (Substrate 4) The substrate 4 is an additional component. The substrate 4 serves to support each layer of the photoelectric conversion element. The substrate 4 can be made of a transparent material. For example, a glass substrate or a plastic substrate can be used as the substrate 4. The plastic substrate can be, for example, a plastic film.

[0066] When the second electrode 9 is light-transmitting, the substrate 4 may be made of a material that does not transmit light. Such a material may be a metal, a ceramic, or a resin material with low light-transmitting properties.

[0067] If the first electrode 5 has sufficient strength, the layers can be supported by the first electrode 5, and therefore the substrate 4 does not need to be provided.

[0068] (1st electrode 5) The first electrode 5 is conductive.

[0069] The first electrode 5 has a translucent property, for example, transmitting light in the visible to near infrared range.

[0070] The first electrode 5 is made of, for example, a transparent and conductive material. Examples of the material are metal oxides or metal nitrides. Examples of such materials are (i) titanium oxide doped with at least one selected from the group consisting of lithium, magnesium, niobium, and fluorine, (ii) gallium oxide doped with at least one selected from the group consisting of tin and silicon, (iii) gallium nitride doped with at least one selected from the group consisting of silicon and oxygen, (iv) tin oxide doped with at least one selected from the group consisting of antimony and fluorine, (v) zinc oxide doped with at least one selected from the group consisting of boron, aluminum, gallium, and indium, (vi) indium-tin composite oxide, or (vii) a composite thereof.

[0071] The first electrode 5 may be formed by providing a light-transmitting pattern. Examples of the light-transmitting pattern include a line-like, wavy-like, lattice-like, or punched metal-like pattern in which a large number of fine through-holes are regularly or irregularly arranged. When the first electrode 5 has these patterns, light can be transmitted through the portion where no electrode material is present. Therefore, by providing a light-transmitting pattern, a non-transparent material can be used. Examples of non-transparent electrode materials are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or an alloy containing any of these. A conductive carbon material may be used as the non-transparent electrode material.

[0072] When the photoelectric conversion element does not include the electron transport layer 6, the first electrode 5 has a blocking property against holes from the photoelectric conversion layer 7. In this case, the first electrode 5 does not have ohmic contact with the photoelectric conversion layer 7. Furthermore, the blocking property against holes from the photoelectric conversion layer 7 means a property that allows only electrons generated in the photoelectric conversion layer 7 to pass and does not allow holes to pass. The Fermi energy of a material having such a property is higher than the energy level of the upper end of the valence band of the photoelectric conversion layer 7. The Fermi energy of a material having such a property may be higher than the Fermi energy of the photoelectric conversion layer 7. A specific example of the material is aluminum.

[0073] When the photoelectric conversion element includes the electron transport layer 6, the first electrode 5 does not need to have a blocking property for holes from the photoelectric conversion layer 7. In this case, the first electrode 5 may be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 7. In this case, the first electrode 5 may or may not be in ohmic contact with the photoelectric conversion layer 7.

[0074] The light transmittance of the first electrode 5 may be, for example, 50% or more, or 80% or more. The wavelength of light that the first electrode 5 should transmit depends on the absorption wavelength of the photoelectric conversion layer .

[0075] The thickness of the first electrode 5 may be, for example, not less than 1 nm and not more than 1000 nm.

[0076] (electron transport layer 6) The electron transport layer 6 includes a semiconductor. The electron transport layer 6 may be formed of a semiconductor having a band gap of 3.0 eV or more. This allows visible light and infrared light to transmit to the photoelectric conversion layer 7. An example of the semiconductor is an inorganic n-type semiconductor.

[0077] Examples of inorganic n-type semiconductors are metal oxides, metal nitrides, or perovskite oxides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. Examples of metal oxides are, for example, TiO 2 or SnO 2 The metal nitride is, for example, GaN. The perovskite oxide is, for example, SrTiO 3 or CaTiO 3 It is.

[0078] The electron transport layer 6 may contain a material having a band gap larger than 6.0 eV. Examples of such materials are (i) alkali metal or alkaline earth metal halides such as lithium fluoride and calcium fluoride, (ii) alkali metal oxides such as magnesium oxide, or (iii) silicon dioxide. In this case, the electron transport layer 6 may have a thickness of, for example, 10 nm or less in order to ensure electron transportability.

[0079] The electron transport layer 6 may include multiple layers made of different materials.

[0080] (Photoelectric conversion layer 7) The photoelectric conversion layer 7 contains a photoelectric conversion material.

[0081] The photoelectric conversion material may be, for example, a perovskite compound. That is, the photoelectric conversion layer 7 may contain a perovskite compound. A perovskite compound has a high light absorption coefficient in the wavelength region of the solar spectrum and a high carrier mobility. Therefore, a photoelectric conversion element containing a perovskite compound has a high photoelectric conversion efficiency.

[0082] Perovskite compounds are, for example, compounds of the formula ABX 3 A is a monovalent cation. Examples of monovalent cations are alkali metal cations or organic cations. Examples of alkali metal cations are potassium cation (K +), Cesium cation (Cs + ), or rubidium cation (Rb + An example of an organic cation is the methylammonium cation (MA + or CH 3 NH 3 + ), formamidinium cation (FA + or HC(NH 2 ) 2 + ), ethylammonium cation (CH 3 CH 2 NH 3 + ), or the guanidinium cation (CH 6 N 3 + ) where B is a divalent cation. An example of a divalent cation is the lead cation (Pb 2+ ) or tin cation (Sn 2+ ) X is a monovalent anion. An example of a monovalent anion is a halogen anion. Each of the A, B, and X sites may be occupied by more than one type of ion.

[0083] The photoelectric conversion material may be, for example, a perovskite compound containing lead.

[0084] The thickness of the photoelectric conversion layer 7 is, for example, not less than 50 nm and not more than 10 μm.

[0085] The photoelectric conversion layer 7 is formed by, for example, a solution coating method, a printing method, or a vapor deposition method. The photoelectric conversion layer 7 may also be formed by cutting out and arranging a perovskite compound.

[0086] The photoelectric conversion layer 7 has a composition formula ABX 3 Here, the photoelectric conversion layer 7 may mainly contain a perovskite compound represented by the composition formula ABX 3 "Mainly containing a perovskite compound represented by the formula ABX" means that the photoelectric conversion layer 7 is 3The photoelectric conversion layer 7 contains 90 mass % or more of a perovskite compound represented by the composition formula ABX 3 The photoelectric conversion layer 7 may contain 95 mass % or more of a perovskite compound represented by the composition formula ABX 3 The photoelectric conversion layer 7 may be made of a perovskite compound represented by the composition formula ABX 3 The perovskite compound may contain defects or impurities.

[0087] The photoelectric conversion layer 7 has a composition formula ABX 3 The perovskite compound may further include another compound different from the perovskite compound represented by the formula (1): An example of the other compound different from the perovskite compound is a compound having a Ruddlesden-Popper type layered perovskite structure.

[0088] (Hole transport layer 8) The hole transport layer 8 contains a hole transport material. The hole transport material is a material that transports holes. The hole transport material is, for example, an organic semiconductor or an inorganic semiconductor.

[0089] The hole transport layer 8 may contain an organic semiconductor. The organic semiconductor forms a good interface with the photoelectric conversion layer 7, and can suppress the occurrence of interface defects during bonding. As a result, the photoelectric conversion element can have high photoelectric conversion efficiency and durability.

[0090] Examples of organic semiconductors are triphenylamine, triallylamine, phenylbenzidine, phenylenevinylene, tetrathiafulvalene, vinylnaphthalene, vinylcarbazole, thiophene, aniline, pyrrole, carbazole, triptycene, fluorene, azulene, pyrene, pentacene, perylene, acridine, or phthalocyanine.

[0091] Representative examples of organic semiconductors used as hole transport materials are 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter also referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl), poly(3,4-ethylenedioxythiophene), or copper phthalocyanine. These organic semiconductors have excellent hole transport properties. Therefore, the photoelectric conversion efficiency of the photoelectric conversion element can be improved.

[0092] The organic semiconductor may include at least one selected from the group consisting of 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].

[0093] Inorganic semiconductors used as hole transport materials are p-type semiconductors. Examples of inorganic semiconductors include Cu. 2 O, CuGaO 2 , CuSCN, CuI, NiO x , MoO x , V 2 O 5 , or a carbon material such as graphene oxide, where x>0.

[0094] The hole transport layer 8 may include multiple layers made of different materials. For example, multiple layers may be laminated so that the ionization potentials of the hole transport layer 8 are successively smaller than the ionization potential of the photoelectric conversion layer 7. This improves the hole transport properties.

[0095] The thickness of the hole transport layer 8 may be 1 nm or more and 1000 nm or less, or 10 nm or more and 50 nm or less. This allows sufficient hole transport properties to be exhibited. Therefore, the solar cell can maintain a low resistance and achieve a high photoelectric conversion efficiency.

[0096] The hole transport layer 8 is formed by, for example, a coating method, a printing method, or a vapor deposition method. This is the same as the photoelectric conversion layer 7. Examples of the coating method are a doctor blade method, a bar coating method, a spray method, a dip coating method, or a spin coating method. An example of the printing method is a screen printing method. If necessary, the hole transport layer 8 may be prepared by mixing a plurality of materials, and then pressed or baked. When the material of the hole transport layer 8 is an organic low molecular weight substance or an inorganic semiconductor, the hole transport layer 8 can also be prepared by a vacuum vapor deposition method.

[0097] The hole transport layer 8 may contain not only a hole transport material but also an additive to increase the conductivity. Examples of the additive are a supporting electrolyte, a solvent, or a dopant. The supporting electrolyte and the solvent have the effect of stabilizing the holes in the hole transport layer 8. The dopant has the effect of increasing the number of holes in the hole transport layer 8.

[0098] Examples of the supporting electrolyte are ammonium salts, alkaline earth metal salts, or transition metal salts. Examples of the ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, or pyridinium salts. Examples of the alkali metal salts are lithium perchlorate or potassium boron tetrafluoride. Examples of the alkaline earth metal salts are calcium(II) bis(trifluoromethanesulfonyl)imide. Examples of the transition metal salts are zinc(II) bis(trifluoromethanesulfonyl)imide or tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt(III) tris(trifluoromethanesulfonyl)imide.

[0099] An example of the dopant is a fluorine-containing aromatic boron compound. An example of the fluorine-containing aromatic boron compound is tris(pentafluorophenyl)borane.

[0100] The solvent contained in the hole transport layer 8 may have excellent ion conductivity. The solvent may be an aqueous solvent or an organic solvent. In order to further stabilize the solute, the solvent contained in the hole transport layer 8 may be an organic solvent. Examples of the organic solvent are heterocyclic compound solvents such as tert-butylpyridine, pyridine, and n-methylpyrrolidone.

[0101] As the solvent, an ionic liquid may be used. The ionic liquid may be used alone or in combination with other solvents. Ionic liquids are desirable because of their low volatility and high flame retardancy.

[0102] Examples of ionic liquids are imidazolium types, such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine types, alicyclic amine types, aliphatic amine types, or azonium amine types.

[0103] The hole transport layer 8 may contain at least one additive selected from the group consisting of tert-butylpyridine, bis(trifluoromethanesulfonyl)imide calcium(II), bis(trifluoromethanesulfonyl)imide zinc(II), tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt(III) tris(trifluoromethanesulfonyl)imide, and tris(pentafluorophenyl)borane. This improves the hole transport properties of the hole transport layer 8. Therefore, the photoelectric conversion efficiency of the photoelectric conversion element can be improved.

[0104] (2nd electrode 9) The second electrode 9 is conductive.

[0105] When the photoelectric conversion element does not include the hole transport layer 8, the second electrode 9 has a blocking property for electrons from the photoelectric conversion layer 7. In this case, the second electrode 9 does not have ohmic contact with the photoelectric conversion layer 7. The blocking property for electrons from the photoelectric conversion layer 7 means a property of passing only holes generated in the photoelectric conversion layer 7 and not passing electrons. The Fermi energy of a material having such a property is lower than the energy level of the lower end of the conduction band of the photoelectric conversion layer 7. The Fermi energy of a material having such a property may be lower than the Fermi energy of the photoelectric conversion layer 7. Specific materials include platinum, gold, and carbon materials such as graphene.

[0106] When the photoelectric conversion element includes a hole transport layer 8, the second electrode 9 does not need to have a blocking property for electrons from the photoelectric conversion layer 7. In this case, the second electrode 9 may be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 7. This allows the second electrode 9 to be formed to have light-transmitting properties.

[0107] Of the first electrode 5 and the second electrode 9, at least the electrode on the side where light is incident needs to be translucent. Therefore, one of the first electrode 5 and the second electrode 9 does not need to be translucent. In other words, one of the first electrode 5 and the second electrode 9 does not need to use a material having translucency, and does not need to have a pattern including openings that transmit light.

[0108] (Porous layer 10) The porous layer 10 is formed, for example, by a coating method on the electron transport layer 6. When the photoelectric conversion element does not include the electron transport layer 6, the porous layer 10 is formed on the first electrode 5.

[0109] The pore structure introduced by the porous layer 10 serves as a base for forming the photoelectric conversion layer 7. The porous layer 10 does not impede the light absorption of the photoelectric conversion layer 7 and the electron transfer from the photoelectric conversion layer 7 to the electron transport layer 6.

[0110] The porous layer 10 includes a porous body.

[0111] The porous body is formed, for example, by a series of insulating or semiconducting particles. Examples of insulating particles are aluminum oxide particles or silicon oxide particles. Examples of semiconducting particles are inorganic semiconductor particles. Examples of inorganic semiconductors are metal oxides, perovskite oxides of metal elements, sulfides of metal elements, or metal chalcogenides. Examples of metal oxides are oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. Metal oxides are, for example, TiO 2 An example of a perovskite oxide of a metal element is SrTiO 3 or CaTiO 3 Examples of sulfides of metallic elements are CdS, ZnS, In 2 S 3 , PbS, Mo 2 S., W.S. 2 , Sb 2 S 3 , Bi 2 S 3 , ZnCdS 2 , or Cu 2 S. Examples of metal chalcogenides are CsSe, In 2 Se 3 , WSe 2 , HgS, PbSe, or CdTe.

[0112] The thickness of the porous layer 10 may be 0.01 μm or more and 10 μm or less, or may be 0.05 μm or more and 1 μm or less.

[0113] The surface roughness of the porous layer 10 may have a surface roughness coefficient of 10 or more, or may be 100 or more, given by effective area / projected area. The projected area is the area of ​​the shadow cast behind an object when it is illuminated with light from the front. The effective area is the actual surface area of ​​the object. The effective area can be calculated from the volume determined from the projected area and thickness of the object, and the specific surface area and bulk density of the material that constitutes the object. The specific surface area is measured, for example, by a nitrogen adsorption method.

[0114] The voids in the porous layer 10 are connected from one main surface of the porous layer 10 to the other main surface of the porous layer 10. That is, the voids in the porous layer 10 are connected from the main surface of the porous layer 10 in contact with the photoelectric conversion layer 7 to the main surface of the porous layer 10 in contact with the electron transport layer 6. This allows the material of the photoelectric conversion layer 7 to fill the voids in the porous layer 10 and reach the electron transport layer 6. Therefore, even if the porous layer 10 is provided, the photoelectric conversion layer 7 and the electron transport layer 6 are in direct contact with each other, so that electrons can be exchanged.

[0115] By providing the porous layer 10, the effect of easily forming the photoelectric conversion layer 7 is obtained. By providing the porous layer 10, the material of the photoelectric conversion layer 7 penetrates into the voids of the porous layer 10, and the porous layer 10 becomes a foothold for the photoelectric conversion layer 7. Therefore, the material of the photoelectric conversion layer 7 is unlikely to be repelled or aggregated on the surface of the porous layer 10. Therefore, the photoelectric conversion layer 7 can be easily formed as a uniform film. The photoelectric conversion layer 7 can be formed by the above-mentioned coating method, printing method, vapor deposition method, or the like.

[0116] It is expected that the light scattering caused by the porous layer 10 will have the effect of increasing the optical path length of the light passing through the photoelectric conversion layer 7. When the optical path length increases, the amount of electrons and holes generated in the photoelectric conversion layer 7 is expected to increase.

[0117] (Middle Class 11) The intermediate layer 11 is made of fullerene (C 60 ), C 60 Derivatives, or C 60 The intermediate layer 11 includes a self-assembled monolayer having a structure of C60 (hereinafter, also referred to as "C60SAM"). Since the intermediate layer 11 efficiently collects electrons, the resistance loss during the transport of electrons to the electron transport layer 6 is reduced.

[0118] C 60 An example of a derivative is [6,6]-Phenyl C 61 butyric acid methyl ester or [6,6]-Phenyl-C 61butyric acid butyl ester. An example of C60SAM is 4-(1',5'-Dihydro-1'-methyl-2'H-[5,6]fullereno-C 60 -Ih-[1,9-c]pyrrol-2′-yl)benzoic acid, (1,2-Methanofullerene C 60 )-61-carboxylic acid, or C 60 Pyrrolidine tris-acid.

[0119] The intermediate layer 11 is formed by, for example, a solution coating method, a dipping method, a printing method, or a vapor deposition method.

[0120] Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.

[0121] In the examples and comparative examples, perovskite solar cells were fabricated, and the initial characteristics of the solar cells, the characteristics after a light resistance test, and the characteristics after a heat resistance test were evaluated.

[0122] The configurations of the photoelectric conversion elements in the solar cells of Examples 1, 4, and 6 and Comparative Example 1 are as follows. Substrate: Glass substrate (thickness: 0.7 mm) First electrode: transparent electrode (indium-tin composite oxide layer) (thickness: 100 nm) Electron transport layer: Titanium oxide (TiO 2 )(Thickness: 30nm) Porous layer: Mesoporous titanium dioxide (TiO 2 ) (thickness: 150 nm) and a mixed layer of the following photoelectric conversion layer material ·Photoelectric conversion layer: HC(NH 2 ) 2 PbI 3 Layer mainly containing (thickness: 500 nm) Hole transport layer: layer containing phenethylammonium iodide (manufactured by greatcellSolar) / layer mainly containing PTAA (however, lithium bis(trifluoromethanesulfonyl)imide (manufactured by Sigma-Aldrich) and 4-tertbutylpyridine are included as additives) (thickness: 50 nm) Second electrode: Au (thickness: 200 nm)

[0123] The configurations of the photoelectric conversion elements in the solar cells of Examples 2, 3, 5, and 7 and Comparative Example 2 are as follows. Substrate: Glass substrate (thickness: 0.7 mm) First electrode: transparent electrode (indium-tin composite oxide layer) (thickness: 100 nm) Electron transport layer: Titanium oxide (TiO 2 )(Thickness: 30nm) Porous layer: Mesoporous titanium dioxide (TiO 2 ) ·Middle layer: 4-(1′,5′-Dihydro-1′-methyl-2′H-[5,6]fullereno-C 60 -Ih-[1,9-c]pyrrol-2'-yl)benzoic acid (i.e., C60SAM) (manufactured by Sigma-Aldrich) (thickness: 50 nm (thickness including mesoporous titanium oxide)), and further containing the material of the photoelectric conversion layer in the voids.) ·Photoelectric conversion layer: HC(NH 2 ) 2 PbI 3 Layer mainly containing (thickness: 500 nm) Hole transport layer: layer containing n-butylammonium bromide (manufactured by GreatcellSolar) / layer mainly containing PTAA (however, tris(pentafluorophenyl)borane (manufactured by Tokyo Chemical Industry Co., Ltd.) is included as an additive) Second electrode: Au (thickness: 200 nm)

[0124] As described above, the photoelectric conversion element in the solar cells according to Examples 1, 4, and 6, and Comparative Example 1 was the photoelectric conversion element of the second configuration example shown in Fig. 3. Moreover, the photoelectric conversion element in the solar cells according to Examples 2, 3, 5, and 7, and Comparative Example 2 was the photoelectric conversion element of the third configuration example shown in Fig. 4.

[0125] <Fabrication of photoelectric conversion element> Example 1 First, a glass substrate having a thickness of 0.7 mm was prepared, which serves as a support material for the solar cell of the present disclosure.

[0126] A layer of indium-tin composite oxide was formed on the substrate by sputtering, thus forming a first electrode.

[0127] Next, a titanium oxide layer was formed on the first electrode by sputtering, thus forming an electron transport layer.

[0128] 30NR-D (Great Cell Solar) was applied onto the electron transport layer by spin coating, and then baked at 500°C for 30 minutes to form a titanium oxide layer having a mesoporous structure. In this way, a porous layer was formed.

[0129] Next, the substrate on which the porous layer was formed was immersed in a C60SAM solution for 30 minutes and then removed. The C60SAM solution was a mixture of tetrahydrofuran (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) and ethanol (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) in a volume ratio of 1:1, to which C60SAM was added at a concentration of 1×10 -5 The substrate was added so that the concentration of C60SAM was mol / L. The removed substrate was thoroughly rinsed with an ethanol solution and then annealed on a hot plate at 100°C for 30 minutes. After annealing, the substrate was naturally cooled to room temperature to obtain a substrate modified with C60SAM. In this way, the intermediate layer was formed.

[0130] Next, a raw material solution of a photoelectric conversion material was applied by spin coating to form a photoelectric conversion layer containing a perovskite compound. The raw material solution was a solution containing 0.92 mol / L lead iodide (II) (Tokyo Chemical Industry Co., Ltd.), 0.17 mol / L lead bromide (II) (Tokyo Chemical Industry Co., Ltd.), 0.83 mol / L formamidinium iodide (GreatCell Solar Co., Ltd.), 0.17 mol / L methylammonium bromide (GreatCell Solar Co., Ltd.), 0.05 mol / L cesium iodide (Iwatani Corporation), and 0.05 mol / L rubidium iodide (Iwatani Corporation). The solvent of the solution was a mixture of dimethyl sulfoxide (acros Co., Ltd.) and N,N-dimethylformamide (acros Co., Ltd.). The mixture ratio (DMSO:DMF) of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF) in this raw material solution was 1:4 by volume.

[0131] Next, a hole transport layer was formed on the photoelectric conversion layer. An isopropyl alcohol (manufactured by Acros Organics) solution containing 1 g / L of phenethylammonium iodide (manufactured by greatcellSolar) was prepared and spin-coated on the photoelectric conversion layer. This formed a layer containing phenethylammonium iodide. Next, a solution containing PTAA was applied by spin-coating to form a layer mainly containing PTAA. The solvent of the solution containing PTAA was toluene (manufactured by Acros). The solution containing PTAA contained 10 g / L of PTAA, lithium bis(trifluoromethanesulfonyl)imide, and 4-tertbutylpyridine.

[0132] Next, an Au film was deposited on the hole transport layer by vacuum deposition to form a second electrode 9. In this manner, a photoelectric conversion element was obtained on the glass substrate as a support material.

[0133] Next, the photoelectric conversion element according to Example 1 was sealed in a glove box in which the water vapor concentration was adjusted to 100 ppm. Here, the oxygen concentration in the glove box was 2 ppm or less. The photoelectric conversion element according to Example 1 was sealed with a UV curing resin, a cover glass, and a glass substrate. That is, the photoelectric conversion element including the first electrode, the electron transport layer, the porous layer, the photoelectric conversion layer, the hole transport layer, and the second electrode was sealed with a UV curing resin, a cover glass, and a glass substrate. As a result, the solar cell according to Example 1 was obtained. In the photoelectric conversion element according to Example 1, the water vapor concentration in the sealed space was 100 ppm, and the oxygen concentration was 2 ppm or less.

[0134] Example 2 A solar cell was fabricated in the same manner as in Example 1, except that the materials used for forming the intermediate layer and for fabricating the hole transport layer were different from those in Example 1. The materials used for forming the intermediate layer and for fabricating the hole transport layer are as follows.

[0135] The intermediate layer was formed by the following procedure. The substrate on which the porous layer was formed in the same manner as in Example 1 was immersed in a C60SAM solution for 30 minutes and then removed. The C60SAM solution was prepared by dissolving C60SAM in a mixed solution of tetrahydrofuran (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) and ethanol (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) in a volume ratio of 1:1, with the concentration of 1×10 -5 The substrate was added so that the concentration of C60SAM was mol / L. The removed substrate was thoroughly rinsed with an ethanol solution and then annealed on a hot plate at 100°C for 30 minutes. After annealing, the substrate was naturally cooled to room temperature to obtain a substrate modified with C60SAM. In this way, the intermediate layer was formed.

[0136] As a solution for forming a layer containing n-butylammonium bromide of the hole transport layer, n-butylammonium bromide (manufactured by greatcellSolar) was used instead of phenethylammonium iodide in the solution containing phenethylammonium iodide used in Example 1. In addition, as a solution for forming a layer mainly containing PTAA, a solution was used in which tris(pentafluorophenyl)borane was used instead of lithium bis(trifluoromethanesulfonyl)imide and 4-tertbutylpyridine in the solution containing PTAA used in Example 1. Other than this, the hole transport layer was formed in the same manner as in Example 1.

[0137] In this manner, the solar cell according to Example 2 was obtained.

[0138] Example 3 In Example 3, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 500 ppm. A solar cell according to Example 3 was obtained in the same manner as in Example 2 except for this.

[0139] Example 4 In Example 4, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 1000 ppm. Other than this, the solar cell according to Example 4 was obtained in the same manner as in Example 1.

[0140] Example 5 In Example 5, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 1000 ppm. Other than this, the same procedure as in Example 2 was carried out to obtain a solar cell according to Example 5.

[0141] Example 6 In Example 6, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 5000 ppm. Other than this, the same procedure as in Example 1 was carried out to obtain a solar cell according to Example 6.

[0142] Example 7 In Example 7, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 5000 ppm. Other than this, the same procedure as in Example 2 was carried out to obtain a solar cell according to Example 7.

[0143] Comparative Example 1 In Comparative Example 1, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 10 ppm. Other than this, the same procedures as in Example 1 were carried out to obtain a solar cell according to Comparative Example 1.

[0144] Comparative Example 2 In Comparative Example 2, the photoelectric conversion element was sealed in a glove box in which the water vapor concentration was adjusted to 10 ppm. Other than this, the same procedures as in Example 2 were carried out to obtain a solar cell according to Comparative Example 2.

[0145] <Photoelectric conversion efficiency measurement> The photoelectric conversion efficiencies of the solar cells according to Examples 1 to 7 and Comparative Examples 1 and 2 were measured.

[0146] The photoelectric conversion efficiency of the solar cell was measured in the initial state, after a light resistance test, and after a heat resistance test using an electrochemical analyzer (ALS440B, manufactured by BAS) and a xenon light source (BPS X300BA, manufactured by Bunkoukeiki). Before the measurement, the light intensity was adjusted to 1 Sun (100 mW / cm) using a silicon photodiode. 2 The current-voltage characteristics were measured at a voltage sweep rate of 100 mV / s. No preconditioning such as light irradiation or long-term forward bias application was performed before the start of the measurement. The aperture was set to 0.1 cm to fix the effective area and reduce the effect of scattered light. 2 The solar cell was masked with a black mask and irradiated with light from the mask / substrate side. The output under the current-voltage conditions that maximized the power was taken as the photoelectric conversion efficiency. The photoelectric conversion efficiency was measured at room temperature in dry air (<2% RH).

[0147] <Light resistance test> A light resistance test was carried out on the solar cells according to Examples 1 to 7 and Comparative Examples 1 and 2. In the light resistance test, the output value was measured while maintaining the voltage and current of the solar cell near the operating point where the output was maximum. Light equivalent to 1 Sun was irradiated from the substrate side for 90 hours while maintaining the substrate temperature at 50°C. After the light resistance test, the photoelectric conversion efficiency of the solar cell was measured by the method described above.

[0148] <Heat resistance test> A heat resistance test was carried out on the solar cells according to Examples 1 to 7 and Comparative Examples 1 and 2. The solar cells were maintained at 85° C. for 190 hours in a thermostatic chamber. After the heat resistance test, the photoelectric conversion efficiency of the solar cells was measured by the method described above.

[0149] The results of the above experiments, that is, the measurement results of the photoelectric conversion efficiency of the solar cell in the initial state, after the light resistance test, and after the heat resistance test, are shown in Table 1. In the table, the additives contained in the raw material solution of the hole transport layer are represented as "LiTFSI" for lithium bis(trifluoromethanesulfonyl)imide and "TPFPB" for tris(pentafluorophenyl)borane. In addition, in order to evaluate the difference in efficiency due to the water vapor concentration for each additive, Table 1 shows the rate of decrease in efficiency when the maximum efficiency of each additive is used as the standard. The rate of decrease in efficiency when the maximum efficiency of each additive is used as the standard is represented in the table as "rate of decrease in conversion efficiency."

[0150] [Table 1]

[0151] In order to compare the effect of water vapor concentration on durability for the efficiency after the light resistance test and the heat resistance test for each additive, the normalized photoelectric conversion efficiency was calculated based on the photoelectric conversion efficiency at the water vapor concentration that showed the maximum efficiency after the test.

[0152] Fig. 5 is a graph showing the water vapor concentration dependence of the normalized photoelectric conversion efficiency of the solar cells of Example 1, Example 4, Example 6, and Comparative Example 1. That is, Fig. 5 is a graph showing the water vapor concentration dependence of the normalized photoelectric conversion efficiency when the additive in the hole transport layer is LiTFSI.

[0153] Fig. 6 is a graph showing the water vapor amount dependency of the normalized photoelectric conversion efficiency of the solar cells of Example 1, Example 4, Example 6, and Comparative Example 1. That is, Fig. 6 is a graph showing the water vapor amount dependency of the normalized photoelectric conversion efficiency when the additive in the hole transport layer is LiTFSI. Fig. 6 shows the horizontal axis of Fig. 5 converted from the water vapor concentration in the sealed space to the value obtained by dividing the water vapor amount by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space.

[0154] Fig. 7 is a graph showing the water vapor concentration dependence of the normalized photoelectric conversion efficiency of the solar cells of Example 2, Example 3, Example 5, Example 7, and Comparative Example 2. That is, Fig. 7 is a graph showing the water vapor concentration dependence of the normalized photoelectric conversion efficiency when the additive in the hole transport layer is TPFPB.

[0155] Fig. 8 is a graph showing the water vapor amount dependency of the normalized photoelectric conversion efficiency of the solar cells of Example 2, Example 3, Example 5, Example 7, and Comparative Example 2. That is, Fig. 8 shows the water vapor amount dependency of the normalized photoelectric conversion efficiency when the additive in the hole transport layer is LiTFSI. Fig. 8 shows the horizontal axis of Fig. 7 converted from the water vapor concentration in the sealed space to the value obtained by dividing the water vapor amount by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space.

[0156] The volume of the sealed space in the solar cells of the examples and comparative examples is approximately 1.4×10 -7 m 3 The surface area of ​​the photoelectric conversion element facing the sealed space is 2.6 × 10 -4 m 2 It was.

[0157] <Effect of water vapor concentration on initial solar cell characteristics> As shown in Table 1, the initial photoelectric conversion efficiency did not differ significantly when the water vapor concentration in the sealed space was 5000 ppm or less, and was stable in the absence of light irradiation or heating.

[0158] <Effect of water vapor concentration on solar cell characteristics after light resistance test> As shown in Table 1, FIG. 5, and FIG. 7, it was found that the photoelectric conversion efficiency after the light resistance test was good when the water vapor concentration in the sealed space was in the range of 100 ppm or more and 5000 ppm or less. On the other hand, the photoelectric conversion efficiency was significantly decreased in the low water vapor concentration region of 10 ppm and when the additive was lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). From the graph in FIG. 5, it is estimated that in the concentration region of water vapor exceeding 5000 ppm, the photoelectric conversion efficiency is lower than the photoelectric conversion efficiency when the water vapor concentration is 5000 ppm. When the water vapor concentration exceeds 5000 ppm, it is considered that the degradation phenomenon induced by excess moisture causes a large amount of decomposition products of the perovskite compound (e.g., metal iodides) to be generated on the surface and / or grain boundaries of the perovskite compound, inhibiting carrier movement. On the other hand, when the water vapor concentration is 5000 ppm or less, the decomposition products contribute to the termination of defects in the perovskite compound, suppressing the photodegradation phenomenon induced by defects in the photoelectric conversion material, and thus suppressing the decrease in photoelectric conversion efficiency. However, when the water vapor concentration is 10 ppm or less, the defects under light irradiation are not sufficiently terminated, the conductivity of PTAA decreases, the hole transport efficiency decreases, and the carrier recombination due to the defect level decreases the solar cell characteristics. In addition, when the PTAA additive was lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), the efficiency decrease rate was large. This is because the doping amount of LiTFSI is smaller than when TFPPB, a strong acceptor molecule, is added, so the high resistance of PTAA due to the low water vapor concentration is significantly manifested, and the effect of increased recombination due to the deterioration of the perovskite compound is large.

[0159] <Effect of water vapor concentration on solar cell characteristics after heat resistance test> As shown in Table 1, Figure 5, and Figure 7, it was found that the photoelectric conversion efficiency after the heat resistance test was good when the water vapor concentration in the sealed space was in the range of 100 ppm or more and 5000 ppm or less. On the other hand, the rate of decrease in the photoelectric conversion efficiency was large in the low water vapor concentration region of 10 ppm. The reason for the existence of an optimal water vapor concentration range is the same for the light resistance test and the heat resistance test. However, unlike the light resistance test, in the heat resistance test, the rate of decrease in the photoelectric conversion efficiency was large when the additive was tris(pentafluorophenyl)borane. This is thought to be because the doping ability of tris(pentafluorophenyl)borane decreases under heating, and the difference in the high conductivity effect of moisture on PTAA becomes apparent. Therefore, by increasing the energy of the light irradiated in the light resistance test and the heating temperature in the heat resistance test, new defects may occur depending on the activation energy of various defect formation, and when the water vapor concentration is low, the conductive properties of PTAA are reduced, and the hole extraction efficiency is reduced, which increases the defect recombination probability and reduces the photoelectric conversion efficiency. However, since the conditions of the light resistance test and heat resistance test in this embodiment were set assuming actual operation outdoors, the optimal water vapor concentration range found by the embodiment for improving the durability of the solar cell remains unchanged.

[0160] From the above results, it was confirmed that the light stability and thermal stability of the solar cell of the present disclosure can be achieved simultaneously when the water vapor concentration in the sealed space is in the range of 100 ppm or more and 5000 ppm or less. [Industrial Applicability]

[0161] INDUSTRIAL APPLICABILITY The present disclosure can significantly improve the durability of solar cells and has extremely high industrial applicability. [Explanation of symbols]

[0162] 1 Photoelectric conversion element 2 Support material 3. Encapsulating material 4. Board 5 1st electrode 6 Electron transport layer 7 Photoelectric conversion layer 8 Hole transport layer 9 Second electrode 10 Porous layer 11 Middle Class 100, 200, 300 Photoelectric conversion element 1000 solar cells

Claims

1. supporting material, A photoelectric conversion element, and a sealing material; the photoelectric conversion element is disposed inside a sealed space sealed by the support material and the sealing material, the photoelectric conversion element includes a first electrode, a photoelectric conversion layer, and a second electrode in this order; The value obtained by dividing the amount of water vapor in the sealed space by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space is 2.3×10 -6 mol / m 2 Greater than or equal to 1.2 x 10 -4 mol / m 2 Below is the Solar cell.

2. The value obtained by dividing the amount of water vapor in the sealed space by the surface area of ​​the surface of the photoelectric conversion element facing the sealed space is 2.3×10 -6 mol / m 2 Greater than or equal to 2.3 x 10 -5 mol / m 2 Below is the The solar cell according to claim 1 .

3. The oxygen concentration in the sealed space is less than 10 ppm by volume fraction. The solar cell according to claim 1 or 2.

4. The partial pressure of water vapor in the sealed space is 1×10 -4 atm or more and 5 x 10 -3 atm. The solar cell according to claim 1 .

5. The photoelectric conversion layer contains a perovskite compound. The solar cell according to claim 1 .

6. The perovskite compound contains lead. The solar cell according to claim 5 .

7. The photoelectric conversion element further includes a hole transport layer disposed between the photoelectric conversion layer and the second electrode, The hole transport layer comprises an organic semiconductor. The solar cell according to claim 1 .

8. The organic semiconductor includes at least one selected from the group consisting of 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]; The solar cell according to claim 7.

9. The hole transport layer further comprises an additive. The solar cell according to claim 7 or 8.

10. The additive comprises at least one selected from the group consisting of tert-butylpyridine, bis(trifluoromethanesulfonyl)imide calcium(II), bis(trifluoromethanesulfonyl)imide zinc(II), tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt(III) tris(trifluoromethanesulfonyl)imide, and tris(pentafluorophenyl)borane; The solar cell according to claim 9.

11. A photoelectric conversion element including a first electrode, a photoelectric conversion layer, and a second electrode in this order is sealed in a sealed space with a water vapor amount of 2.3×10 per surface area of ​​the surface of the photoelectric conversion element facing the sealed space. -6 mol / m 2 Greater than or equal to 1.2 x 10 -4 mol / m 2 and sealing in an atmosphere controlled to: How solar cells are manufactured.

Citation Information

Patent Citations

  • High-efficiency perovskite solar cell and preparation method thereof

    CN111640870A

  • Undoped organic-small-molecule hole transport material, perovskite solar cell, and preparation method and application of perovskite solar cell

    CN112552311A

  • Method for manufacturing photoelectric conversion device

    JP2017216270A

  • Solar battery module

    JP2019021913A

  • Light-absorbing material and solar cell using the same

    JP2019125775A